An Asymmetric-Error-Aware LDPC Decoding Algorithm for DNA Storage - Sun, Yi; Han, Guojun; Liu, Chang; Wang, Yixin; Fang, Yi (IEEE communications letters, 2023)
With the rapid growth of data, DNA is attracting attention as a promising storage medium due to its durability, large storage capacity, and high bulk density. However, errors occur in DNA synthesis and sequencing processes, with substitutions being the most common errors in DNA storage process. To address this issue, we select low-density parity-check (LDPC) codes as the error correction method to guarantee data reliability. However, unlike traditional data storage channels, errors occurring between nucleotides in the DNA channel are asymmetric. Therefore, traditional belief propagation (BP) decoding algorithm is not sufficient for effective error correction under DNA channel. In this letter, we propose to use two LDPC codes and take error types as additional information for calibrating log-likelihood ratio (LLR) value. In addition, compared with previous works, simulation results show that our proposed decoding algorithm can reduce bit error rate (BER) by 33% ~ 94%.